2022
DOI: 10.1111/ped.14895
|View full text |Cite
|
Sign up to set email alerts
|

Change in children's perception of cancer in the last 10 years in Japan

Abstract: Background Social awareness of cancer can be changed with cancer education and proper distribution of cancer information. This study addressed the current situation and historical changes to children's perception of cancer. Methods Questionnaire surveys were conducted among healthy school children aged 10–15 years in 2008 and 2018. Knowledge of cancer was surveyed and compared with that of asthma, tuberculosis, and measles. The children were asked about their health information resources. Results The numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Despite both Korea and Japan being part of East Asia, a 2018 Japanese study on middle school students' perceptions of cancer revealed discrepancies with our findings for the same age group [ 15 ]. The study showed that more middle school students agreed on the effects of cancer on adolescents and its severity, while the rates of consent on contagiousness, preventability, and curability were lower than those in our study [ 15 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Despite both Korea and Japan being part of East Asia, a 2018 Japanese study on middle school students' perceptions of cancer revealed discrepancies with our findings for the same age group [ 15 ]. The study showed that more middle school students agreed on the effects of cancer on adolescents and its severity, while the rates of consent on contagiousness, preventability, and curability were lower than those in our study [ 15 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Despite both Korea and Japan being part of East Asia, a 2018 Japanese study on middle school students' perceptions of cancer revealed discrepancies with our findings for the same age group [ 15 ]. The study showed that more middle school students agreed on the effects of cancer on adolescents and its severity, while the rates of consent on contagiousness, preventability, and curability were lower than those in our study [ 15 ]. A big difference in health information resources was also observed between the two countries, with ROK’s main sources being the Internet and television, while that for Japan were television, parents, books, Internet, and teachers [ 15 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations